The Influence of Financial Technology on Changes in Consumer Behavior - Soedarwati, Ernie (Journal of Management, 2024)
The purpose of this study is to investigate the role of Fintech Lending in promoting the growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The analysis results suggest that the regression model utilized has high statistical significance, with a significant F value (Sig. = 0.000). Only the frequency with which Fintech services are used was found to have a significant impact on MSME growth (Sig. = 0.003). The factors Access to Fintech and Number of Landing did not have a meaningful influence. The Adjusted R Square score of 0.307 indicates that this model can explain 30.7% of the variability in MSME growth, implying that there are more variables outside the model that influence MSME growth.The findings emphasize the relevance of frequency of use of Fintech services in promoting MSME growth and recommend that Fintech service providers improve their tactics to enhance MSMEs' adoption and repeated use of services. This study also proposes additional research to uncover other factors that influence MSME growth in the context of Fintech lending.